The Blessing of Abraham: Seeking an Interpretive Link between Genesis 12:1-3 and Galatians 3:13-16 - Toryough, G. N. (Ilorin journal of religious studies, 2014)
God promised to bless not only Abraham, in Genesis 12:1-3, but to also bless all the families of the earth through him. And in Galatians 3:13-14, Paul relates this blessing as being bestowed upon the Gentiles through the redemptive work of Jesus Christ on the cross. Many prosperity preachers interpret the Abrahamic blessing as prospering in material and financial abundance. They also assert that it is salvation through Jesus Christ that gives Christians, who are Abraham’s spiritual children, access to the Abrahamic blessing. But when these biblical passages mentioning the Abrahamic blessing were interpreted within the context of Paul’s understanding of the blessing and using a theological method of biblical interpretation that incorporates a synchronic method of biblical exegesis with the sub-method of lexical and syntactic analysis, it was found out that the blessing is that of sonship through Jesus Christ by virtue of the gift of the Holy Spirit and not material or financial blessing.